MODEL KONSELING MELALUI PSIKODRAMA UNTUK MENINGKATKAN POTENSI MAHASISWA PSIKOLOGI ANGKATAN - Safitri, Safitri (Jurnal Psikologi, 2013)
AbstractCounseling is needed for new students who are experiencing changes in the learning process. Individual counseling has not been a requirement for new students, on the other hand the results of the first year will determine the success of next year. There are many students who can not open the problem in individual counseling. So group counseling will be required , which is  psychodrama as the technique . Healing Theatre  is part of the psychodrama that expected to be the entrance to the implementation of group counseling. Results of this study showed that the Healing Theatre can be used as a guidance group.  which 100 % regular students and 73% of executives stated that for Healing Theatre suitable for  a group counselin. The results showed  that students can feel the change in both the expression and feelings with color, and statement of whether there is a problem that can not be expressed and differ significantly. To levels no statement / its not a problem that can not be told also differ significantly . Keywords: group counseling, psychodrama, healing theatre